Meristem Genes in the Highly Reduced Endoparasitic Pilostyles boyacensis (Apodanthaceae) - González, Angie D.; Pabón-Mora, Natalia; Alzate, Juan F.; González, Favio (Frontiers in Ecology and Evolution, 2020)
The family Apodanthaceae comprises two genera (Apodanthes and Pilostyles) and 14 endoparasitic species, all of them lacking root and shoot apical meristems, stems and leaves. Their vegetative phase is reduced to a mycelium-like endophyte formed by strands of parenchyma cells that are in close contact to the host vasculature. These plants become apparent only when their tiny gregarious flowers emerge breaking through the host cortex. The lack of vegetative meristems in these plants sharply contrasts to the typical formation of floral meristems. Our target species, Pilostyles boyacensis, provides a suitable system to investigate the evolution of meristem –related genes in an endoparasitic flowering plant without a typical vegetative shoot apical meristem. We have generated transcriptomes from two different developmental stages of the parasite (emerged floral buds and fruits), as well as a mixed sample that comprises the endophyte and growing floral buds of the parasite and its host, Dalea cuatrecasasii (Fabaceae). We specifically assessed copy number and domain conservation for the WUSCHEL HOMEOBOX, LRR-RLK-IX-a, and CLE families related to the maintenance of the shoot apical meristem (SAM) as well as the ARF and LFY families responsible for floral meristem identity. Five out of the 11 canonical gene families responsible for SAM maintenance and floral fate determinacy targeted in this study were found in Pilostyles. P. boyacensis shows at least one transcript with all functional domains conserved for BAM1, WUS, WOX9, ARF7 and LFY. Other genes implicated in the canonical regulatory network could not be found, including ARF5, ARF19, BAM2, BAM3, CLV1, and CLV3. In conclusion, the endoparasitic lifestyle of Apodanthaceae appears to correlate with a substantial reduction in the transcriptomic machinery linked to SAMs, whereas the genes involved in flower fate have remained intact.